RETRACTED: The role of world’s natural-science picture formation in the professional thinking development process of aquaculture specialists - Neidorf Anna; Tkacheva Irina; Kokhanov Yuriy; Morozova Marina; Abrosimova Ekaterina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001